Working with children with cortical visual impairment who use augmentative and alternative communication: implications for improving current practice. (3rd April 2022) - Luo, Fei; Blackstone, Sarah W.; Canchola, Jesse; Roman-Lantzy, Christine
Abstract: The aim of this study was to describe how professionals from multiple disciplines (e.g., speech-language pathologists, teachers, occupational therapists) in the United States reported challenges they face in delivering services to children with cortical visual impairment (CVI) who use augmentative and alternative communication (AAC). Three surveys were utilized to identify barriers to and priorities for improving educational and clinical services and in-service and preservice education from the perspectives of professionals in school, community, and university settings. Results suggest that current service delivery models may not be meeting the needs of either children with CVI who use AAC or the professionals whose job it is to provide them with services. Professionals in community-based settings appeared to encounter more barriers. Findings help to support a discussion about approaching AAC interventions for children with CVI who use AAC by adopting interprofessional collaborative practice (IPCP) and interprofessional education (IPE) models, which reflect long-standing best practice guidelines for AAC service delivery and are encouraged by multiple professional organizations.